Multi‐centre retrospective study of long‐term outcomes following traumatic elbow luxation in 37 dogs. (8th June 2016) - Sajik, D.; Meeson, R. L.; Kulendra, N.; Jordan, C.; James, D.; Calvo, I.; Farrell, M.; Kulendra, E.
Abstract : OBJECTIVES: Limited guidelines exist regarding the optimal treatment of traumatic canine elbow luxation, and there is a lack of information on long‐term functional outcome. Here we report reduction and stabilisation techniques for a series of traumatic elbow luxations and describe clinical outcome plus long‐term questionnaire‐based follow‐up. METHODS: Retrospective review of canine traumatic elbow luxations (2006 to 2013) treated at five referral centres. Data recorded included signalment, luxation aetiology, time to reduction, reduction technique, surgical procedure, post‐reduction care and complications. Questionnaire follow‐up was attempted for all cases with owners completing the Canine Brief Pain Inventory. RESULTS: Thirty‐seven dogs were included. The most frequent cause of luxation was road traffic accident (n=22). Twenty cases were treated surgically. Seven dogs suffered major postoperative complications: reluxation (n=6), infection requiring implant removal (n=1). Four of the six reluxations occurred in dogs that had other orthopaedic injuries. Twenty‐two owners completed the Canine Brief Pain Inventory questionnaire: there were 13 excellent, 6 very good, 1 good and 2 fair outcomes. Outcome was not associated with the reduction technique. CLINICAL SIGNIFICANCE: Initial closed reduction, followed by surgical stabilisation if unsuccessful, results in good‐to‐excellent outcomes in the majority of traumatic canine elbow luxations. Reluxation was the most common major complication and there was a higher incidence of reluxation in patients with multiple orthopaedic injuries.